HVDC for Grid Services in Electric Power Systems - Jang, Gilsoo (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The modern electric power system has evolved into a huge nonlinear complex system due to the interconnection of thousands of generation and transmission systems. The unparalleled growth of renewable energy resources (RESs) has caused significant concern regarding grid stability and power quality, and it is essential to find ways to control such a massive system for effective operation. The controllability of HVDC and FACTS devices allows for improvement of the dynamic behavior of grids and their flexibility. Research is being carried out at both the system and component levels of modelling, control, and stability. This Special Issue aims to present novel HVDC topologies and operation strategies to prevent abnormal grid conditions.